Carcinoma hepatocelular em portadores crônicos do vírus da hepatite B: incidência, fatores de risco e acurácia de escores preditores - COSTA, Alessandra Porto de Macedo (2023)
Chronic hepatitis virus (HBV) infection is one of the main risk factors for hepatocellular carcinoma (HCC). The incidence of HCC in HBV carriers, as well as its occurrence in the absence of liver cirrhosis, remains uncertain in Brazil. This study aimed to evaluate the effectiveness of HCC screening in HBV carriers, in a specialized service, in order to identify high-risk patients. Methods: This was a retrospective cohort study involving 1,040 chronic HBV carriers, followed in a single service in a state in northeastern Brazil. The HCC incidence density was calculated considering the new cases that occurred during the study period. Kaplan-Meier analysis was used to estimate the cumulative incidence of HCC. For the analysis of predictors of HCC development, the Cox regression technique was used. Results: Among the 1,040 patients, 53.7% were women and the median age was 48 years. The median follow-up time was 52 months. The median interval between visits was 6.55 months, and in 75% of the sample the interval was up to 8 months and regular follow-up was carried out for at least 96 months. Thirty cases of HCC (2.9%) were identified during follow-up. All cases occurred in cirrhotic patients. The HCC incidence rate for the entire population was 5.3 per 1000 person-years of observation. Only age and positive HBeAg were independently associated with an increased risk of developing HCC. Conclusion: The presence of cirrhosis in all patients who developed HCC in a sample of HBV carriers from a single Brazilian center where surveillance was effective in 75% of the sample, it is a very relevant fact, reinforcing the importance of strict and periodic surveillance in cirrhotic patients.